2018
DOI: 10.1159/000487344
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Overexpression of IL-37 Protects Against Atherosclerosis and Strengthens Plaque Stability

Abstract: Background/Aims: Recently, studies have shown that interleukin-37 (IL-37) is involved in atherosclerosis-related diseases. However, the regulatory mechanisms of IL-37 in atherosclerosis remain unknown. This study aims to determine the role of IL-37 in atherosclerosis and to investigate the underlying mechanisms involved. Methods: IL-37 expression in human atherosclerotic plaques was detected by immunohistochemical staining and real-time reverse transcription polymerase chain reaction (RT-PCR). Oil Red O staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 40 publications
(59 reference statements)
3
24
0
Order By: Relevance
“…However, no differences were found in MMP2 expression. According to the previous studies, IL-37 indeed affects MMP2 and MMP9 expressions in endometriosis, atherosclerosis, and human lung adenocarcinoma [40][41][42]. But why changes only occur in MMP9.…”
Section: Discussionmentioning
confidence: 89%
“…However, no differences were found in MMP2 expression. According to the previous studies, IL-37 indeed affects MMP2 and MMP9 expressions in endometriosis, atherosclerosis, and human lung adenocarcinoma [40][41][42]. But why changes only occur in MMP9.…”
Section: Discussionmentioning
confidence: 89%
“…IL-33 is much greater and IL-37 much lower in all the patients' groups at T0 than in controls. IL-37 inhibits the expression of pro-inflammatory cytokines 28 and in mice exhibited significant improvements in the atherosclerotic burden 29 . Recently it has been suggested a possible role of IL-37 in human sera as a therapeutic agent or biomarker for the diagnosis of cardiovascular diseases 30 .…”
Section: Cytokines Serum Concentrations At the Admission Of Cardiac Rmentioning
confidence: 99%
“…Another anti-inflammatory cytokine IL-37 expression was significantly reduced in the sputum of asthmatic children (Charrad et al, 2016), and was shown to be a key suppressor of asthma mediated mast cells (Conti et al, 2017) and airway inflammation and remodeling (Huang et al, 2018;Meng et al, 2019). IL-37 has also been found to exert athero-protective effects via the modulation of dendritic cell maturation, macrophage activation and by inducing Treg responses (Chai et al, 2015;Ji et al, 2017;McCurdy et al, 2017;Liu et al, 2018). Enhancing the activity of anti-inflammatory cytokines such as IL-10 and IL-37, which have protective roles in both disease states could be another potential avenue for pharmacological intervention for asthmatic patients who develop or are at high risk for developing CVD as a comorbidity.…”
Section: Targeting Cytokinesmentioning
confidence: 99%